Suppressing Charge Recombination and Ultraviolet Light Degradation of Perovskite Solar Cells Using Silicon Oxide Passivation. Issue 12 (26th June 2019) - Ren, Jing; Luo, Qiang; Hou, Qinzhi; Chen, Hui; Liu, Tao; He, Hongcai; Wang, Jinshu; Shao, Qian; Dong, Mengyao; Wu, Shide; Wang, Ning; Lin, Jing; et al.
Abstract: Organic‐metal lead halide perovskite solar cells (PSCs) featuring low‐cost and high efficiency have been recognized as promising photovoltaic devices, but their serious charge recombination and ultraviolet light irradiation instability limit their output efficiency and long‐term operation. In this work, we have introduced silicon oxide as an interfacial modifier of the electron transporting layer in TiO2 ‐based planar heterojunction PSCs. The incorporation of a silicon oxide modifier passivates the trap states of perovskite absorber and suppresses the charge recombination of PSCs. As a consequence, a competitive solar‐to‐electricity conversion efficiency of 18.0 % was achieved for the device fabricated with the silicon‐oxide‐modified TiO2 electron extraction layer, which is increased by 15 % compared with the PSC fabricated with pristine TiO2 ; this can be attributed to the significantly increased open‐circuit voltage and photocurrent density. Furthermore, the ultraviolet light irradiation stability of PSCs is greatly improved, resulting from the low photocatalytic activity of the silicon‐oxide‐modified TiO2 electron transporting layer, as revealed by the photoelectrochemical oxidation of CH3 NH2 . This work represents a feasible step through interfacial engineering toward the realization of ultraviolet‐light‐stable and scalable PSCs. Abstract : Light it up : Retarding charge recombination and ultraviolet light irradiation degradation of lead‐halide perovskite solar cells is highly desirable for their large‐scale application. This work demonstrates that a SiO x interfacial layer inserted between the electron transporting layer and light‐absorber layer passivates the trap states of lead‐halide perovskite and simultaneously suppresses the charge recombination, resulting in an 18 % efficiency output of TiO2 ‐based planar perovskite solar cells and improved light soaking stability under ultraviolet light irradiation.